Pendampingan Belajar Matematika Berbantuan Gim Astromath untuk Siswa MI Nurul Mun’im - Arini Hidayati; Nanda Aqidah Putri; Della Indrian Maharani; Rafiyono Rafiyono (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2026)
This article discusses community service aimed at improving students' mathematical understanding at MI Nurul Mun'im through learning assistance assisted by the Astromath game. The main problem faced is low student motivation and understanding in mathematics, caused by less engaging learning methods. The purpose of this activity is to provide a solution by using innovative educational technology, specifically the Astromath game, which is designed to develop students' mathematical abilities in an interactive and fun way. The method used in this community service is a direct mentoring approach that involves students in game-assisted learning sessions, with mentoring from lecturers and students. This activity was carried out over several meetings involving the direct use of the Astromath game in class. The results obtained showed an increase in student understanding of mathematics material, especially in terms of basic arithmetic operations, as well as a significant increase in learning motivation. This is indicated by an increase in the average pre-test score from 58.8 to 88.9 average post-test score. In addition, students were also more active and interested in participating in mathematics lessons after being involved in learning sessions using this game. The use of the Astromath game has proven effective in making mathematics learning more interesting and improving student learning outcomes at MI Nurul Mun'im.